PseudoCell: A Multivalued Logical Regulatory Network to Investigate Premature Senescence Dynamics and Heterogeneity - Vinícius Pierdoná; Patrícia Lavandoski; Rafael Moura Maurmann; Guilherme Antônio Borges; Jose Carlos Merino Mombach; Fátima Theresinha Costa Rodrigues Guma; Florencia María Barbé‐Tuana (Aging Medicine, 2025)
ABSTRACT Purpose Premature cellular senescence is a pivotal process in aging and age‐related diseases, triggered by various stressors. However, this is not a homogeneous phenotype, but a heterogeneous cellular state composed of multiple senescence programs with different compositions. Therefore, understanding the complex dynamics of senescence programs requires a systemic approach. We introduce PseudoCell, a multivalued logical regulatory network designed to explore the molecular intricacies of premature senescence. Methods PseudoCell integrates key senescence signaling pathways and molecular mechanisms, offering a versatile platform for investigating diverse premature senescence programs initiated by different stimuli. Results Validation through simulation of classical senescence programs, including oxidative stress‐induced senescence and oncogene‐induced senescence, demonstrates its ability to replicate molecular signatures consistent with empirical data. Additionally, we explore the role of CCL11, a novel senescence‐associated molecule, through simulations that reveal potential pathways and mechanisms underlying CCL11‐mediated senescence induction. Conclusions In conclusion, PseudoCell provides a systematic approach to dissecting premature senescence programs and uncovering novel regulatory mechanisms.